The Kyai’s Position in Rural Local Democracy Based on Patronage Politics at Tapal Kuda - Ardhana Januar Mahardhani; Nawiruddin Nawiruddin; Jalaluddin Jalaluddin; Julhadi Julhadi; Muta'allim Muta'allim (Muslim Heritage, 2023)
AbstractSociologically, the village community in the East Java Tapal Kuda is dominated by the sarong people who have affiliation with certain Pesantren either as alumni or only as sympathizers. This is because the distribution of Islamic boarding schools in this area is relatively highand is socio-cultural educational basis of rural communities in the region. The indication is the domination of society Nahdliyin affiliated with Nahdlatul Ulama as a social organization social largest in Indonesia. This study aims to describe the role of Kyai in the context of local democracy rural based on patronage politics in the East Java Tapal Kuda. The method used in this research is descriptive qualitativewith inductive approach. While the type study is a case study. The data collection instruments used were observation, documentation and in-depth interviews. In collecting data, this research uses Miles and Huberman’s interactive model, namely; data reduction, data presentation, drawing conclusions. In testing the validity of the data, researchersuse triangulation, namely source triangulation, method triangulation, peer discussion andmember check. The results of the study show that rural communities are ordinary people who do not have political awareness in local democracy so they are independent patron to Kyai as role models in their lives and the role of the Kyai in the patronage politics of rural communities determines the flow of support for local democratic communities because politics is a subordinate area of the religiosity of rural communities.  AbstrakMasyarakat desa secara sosiologis di Tapal Kuda Jawa Timur didominasi oleh kaum sarungan yang  memiliki afiliasi pada pesantren tertentu baik sebagai alumni maupun hanya sebatas simpatisan. Pasalnya, sebaran pesantren di daerah ini tergolong tinggi dan merupakan basis sosial-budaya pendidikan masyarakat pedesaan di wilayah tersebut. Indikasinya adalah dominasi masyarakat Nahdliyin yang berafiliasi pada Nahdlatul Ulama sebagai organisasi sosial kemasyarakatan terbesar di Indonesia.Penelitian ini bertujuan untuk mendeskripsikan peran Kyai dalam konteks demokrasi lokal pedesaan yang berbasis pada politik patronase di lingkup Tapal Kuda Jawa Timur. Metode yang digunakan dalam penelitian ini adalah kualitatif deskriptif dengan pendekatan induktif. Sedangkan jenis penelitian adalah studi kasus. Instrumen pengumpulan data yang dipakai adalah observasi, dokumentasi dan wawancara secara mendalam.  Dalam pengumpulan data, penelitian ini menggunakan model interaktif Miles dan Huberman, yaitu; reduksi data, penyajian data, penarikan kesimpulan. Dalam uji keabsahaan data, peneliti menggunakan triangulasi, yaitu triangulasi sumber, triangulasi metode, diskusi sejawat dan member check. Hasil penelitian menunjukkan bahwa masyarakat pedesaan adalah masyarakat awam yang tidak memiliki kesadaran politis dalam demokrasi lokal sehingga mereka berpatron pada Kyai sebagai panutan dalam kehidupan mereka dan peran Kyai dalam politik patronase masyarakat pedesaan menentukan terhadap arus dukungan masyarakat demokrasi lokal sebab politik merupakan wilayah subordinat dari religiusitas masyarakat desa.